Church-state separation and challenging issues concerning religion - Batalla, Eric Vincent C. (Animo Repository, 2019)
In its declaration of principles, the 1987 Philippine Constitution provides for the separation of Church and State. While the principle honors distinctions between temporal and spiritual functions, both Church and State maintain a unique and cooperative relationship geared towards the common good. However, traditional boundaries governing political and religious agency have been crossed during Duterte’s presidency causing a conflict between leaders of government and the Catholic hierarchy. In the process, the conflict has resurfaced issues about the principle of Church-State separation. What accounts for the changing Church-State relations in the Philippines? How will this conflict affect State policy towards religion, religious freedom, and religious education? In the present study we discuss the present context of the Church-State separation principle in the Philippines. We argue that institutional relations between Church and State remain stable despite the Duterte-Catholic Church conflict. © 2019 by the author.